2019
DOI: 10.7150/ijms.35369
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Released by Bone Marrow Mesenchymal Stem Cells Attenuate Lung Injury Induced by Intestinal Ischemia Reperfusion via the TLR4/NF-κB Pathway

Abstract: Purpose: Acute lung injury (ALI) is a primary component of multiple organ dysfunction syndromes triggered by intestinal ischemia-reperfusion (IIR) which results in high mortality. Existing treatment options remain unsatisfactory. Mesenchymal stem cells (MSCs) have shown considerable promise as a biological therapy for ALI in preclinical studies. However, there are many limitations to stem cell treatment. This study aimed to investigate whether MSC-derived exosomes, a non-cellular alternative, are able to act i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 36 publications
1
55
0
1
Order By: Relevance
“…Similarly, a study into the role of exosomes in the progression of atherosclerosis employed exosomes derived from oxidized low-density lipoprotein (oxLDL)-stimulated macrophages and revealed that intravenous administration of oxLDL-treated macrophage cell-derived exosomes into male ApoE-deficient atherosclerosis mice significantly deteriorated atherosclerosis in vivo [38]. In another study, MSC-Exo were shown to exert antiapoptotic and anti-inflammatory effects on intestinal ischaemia-reperfusion-induced lung damage; their effects were accompanied by the downregulation of TLR4 and NF-κB expression, which further protected the lungs against ischeamia-reperfusion-induced acute lung injury [39].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, a study into the role of exosomes in the progression of atherosclerosis employed exosomes derived from oxidized low-density lipoprotein (oxLDL)-stimulated macrophages and revealed that intravenous administration of oxLDL-treated macrophage cell-derived exosomes into male ApoE-deficient atherosclerosis mice significantly deteriorated atherosclerosis in vivo [38]. In another study, MSC-Exo were shown to exert antiapoptotic and anti-inflammatory effects on intestinal ischaemia-reperfusion-induced lung damage; their effects were accompanied by the downregulation of TLR4 and NF-κB expression, which further protected the lungs against ischeamia-reperfusion-induced acute lung injury [39].…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence suggested that MSC-Exo could exert effects via activating/inactivating signalling pathways including the TGF-β1 [42], NF-κB [39,43] and Wnt [44] signalling pathways. However, to date, the Erk signalling pathway has rarely been studied with MSC-Exo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more studies illustrate that exosomes from MSCs display beneficial roles in ALI. MSC-derived exosomes protect against intestinal ischemia-induced ALI via inhibition of TLR4/NF-κB signaling 38 and MSCs-exosomes confer protective effects against ALI by inducing the expression of miR-30b-3p 39 . In addition, hucMSCs-exosomes successfully decrease inflammatory factors in rats after burn, and this reduction is reversed by miR-451 expression in hucMSCs-exosomes via the TLR4/NF-κB pathway 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recent references, we learned that MSC reduces epithelial permeability following phosgene-induced ALI through regulating the classical signaling pathways, such as Wnt/β-catenin signaling pathway 31 and NF-κB signaling pathway 32 . Here, we also investigated the effect of MSC on several classical signaling pathways in ALI cell model.…”
Section: Discussionmentioning
confidence: 99%